Tan80 = QR / RS
QR = 5.67 (2)
QR = 11.34
answer
<span>11.34cm</span>
I think the answer is 56.81 seconds, the best time would just be the shortest time
B. 24x2 is the correct answer
The trick is to exploit the difference of squares formula,
![a^2-b^2=(a-b)(a+b)](https://tex.z-dn.net/?f=a%5E2-b%5E2%3D%28a-b%29%28a%2Bb%29)
Set a = √8 and b = √6, so that a + b is the expression in the denominator. Multiply by its conjugate a - b:
![(\sqrt8+\sqrt6)(\sqrt8-\sqrt6)=(\sqrt8)^2-(\sqrt6)^2=8-6=2](https://tex.z-dn.net/?f=%28%5Csqrt8%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%29%3D%28%5Csqrt8%29%5E2-%28%5Csqrt6%29%5E2%3D8-6%3D2)
Whatever you do to the denominator, you have to do to the numerator too. So
![\dfrac{\sqrt2+\sqrt6}{\sqrt8+\sqrt6}=\dfrac{(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)}{(\sqrt8+\sqrt6)(\sqrt8-\sqrt6)}=\dfrac{(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)}2](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csqrt2%2B%5Csqrt6%7D%7B%5Csqrt8%2B%5Csqrt6%7D%3D%5Cdfrac%7B%28%5Csqrt2%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%29%7D%7B%28%5Csqrt8%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%29%7D%3D%5Cdfrac%7B%28%5Csqrt2%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%29%7D2)
Expand the numerator:
![(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=\sqrt{2\cdot8}+\sqrt{6\cdot8}-\sqrt{2\cdot6}-(\sqrt6)^2](https://tex.z-dn.net/?f=%28%5Csqrt2%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%29%3D%5Csqrt%7B2%5Ccdot8%7D%2B%5Csqrt%7B6%5Ccdot8%7D-%5Csqrt%7B2%5Ccdot6%7D-%28%5Csqrt6%29%5E2)
![(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=\sqrt{16}+\sqrt{48}-\sqrt{12}-6](https://tex.z-dn.net/?f=%28%5Csqrt2%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%29%3D%5Csqrt%7B16%7D%2B%5Csqrt%7B48%7D-%5Csqrt%7B12%7D-6)
![(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=4+\sqrt{48}-\sqrt{12}-6](https://tex.z-dn.net/?f=%28%5Csqrt2%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%29%3D4%2B%5Csqrt%7B48%7D-%5Csqrt%7B12%7D-6)
![(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=-2+\sqrt{12}(\sqrt4-1)](https://tex.z-dn.net/?f=%28%5Csqrt2%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%29%3D-2%2B%5Csqrt%7B12%7D%28%5Csqrt4-1%29)
![(\sqrt2+\sqrt6)(\sqrt8-\sqrt6)=-2+\sqrt{12}(2-1)](https://tex.z-dn.net/?f=%28%5Csqrt2%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%29%3D-2%2B%5Csqrt%7B12%7D%282-1%29)
![(\sqrt2+\sqrt6)(\sqrt8-\sqrt6}=-2-\sqrt{12}](https://tex.z-dn.net/?f=%28%5Csqrt2%2B%5Csqrt6%29%28%5Csqrt8-%5Csqrt6%7D%3D-2-%5Csqrt%7B12%7D)
So we have
![\dfrac{\sqrt2+\sqrt6}{\sqrt8+\sqrt6}=-\dfrac{2+\sqrt{12}}2](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csqrt2%2B%5Csqrt6%7D%7B%5Csqrt8%2B%5Csqrt6%7D%3D-%5Cdfrac%7B2%2B%5Csqrt%7B12%7D%7D2)
But √12 = √(3•4) = 2√3, so
![\dfrac{\sqrt2+\sqrt6}{\sqrt8+\sqrt6}=-\dfrac{2+2\sqrt3}2=\boxed{-1-\sqrt3}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csqrt2%2B%5Csqrt6%7D%7B%5Csqrt8%2B%5Csqrt6%7D%3D-%5Cdfrac%7B2%2B2%5Csqrt3%7D2%3D%5Cboxed%7B-1-%5Csqrt3%7D)
Answer:
1/6, because there is only one way it's possible and there are 6 outcomes.
Step-by-step explanation: